Analisis Pengaruh Kualitas Sistem Informasi Akuntansi Terhadap Penerimaan Teknologi Pada Sektor UMKM Medan Tuntungan - Eni Duwita Sigalingging (Mahesa Research Center, 2022)
Micro, Small and Medium Enterprises (MSMEs) adopt information technology if MSME users see perceived usefulness and perceived usefulness in utilizing high-quality IT-based accounting information systems. The aim is to analyze the effect of the quality of accounting information systems on perceived ease of use in the MSME sector in Medan Tuntungan; to analyze the effect of perceived ease of use on perceived usefulness in the Medan Tuntungan MSME sector, to analyze the effect of the quality of accounting information systems on perceived usefulness through perceived ease of use in the Medan Tuntungan MSME sector. The population is 50 people, and all of them are sampled in what is called a census or population study. Furthermore, the data collected from the respondents were evaluated descriptively using Structural Equation Modeling (SEM) and Partial Least Square (PLS) regression. The results of the study are (1) the quality of the information system affects the perceived ease of use at a significant level of 25,727; (2) the quality of the information system has an effect on perceived usefulness at a significant level of 25,630; (3) perceived ease of use has an effect on perceived usefulness at a significant level of 3,642.